2021
DOI: 10.3332/ecancer.2021.1223
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive comparison between young and older-age non-small cell lung cancer patients at a public referral centre in Delhi, India

Abstract: Purpose Given the increasing number of non-small cell lung cancer (NSCLC) patients in India, a comparative analysis between patients under 40 years and those of older age at a major public referral centre would provide insight into the phenotypic patterns of this group. Methods NSCLC patients who were accessioned within the lung cancer clinic database of the Pulmonary Medicine Department at the all India institute of medical sciences – Delhi between 2008 and 2019 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 28 publications
5
25
0
Order By: Relevance
“…Therefore, the ADC histology subtype dominated in this population. No sex differences were observed in our study, which was similar to several other studies (4,9,23). Our study showed that when compared with the older cohort, younger patients were more likely to be diagnosed at advanced stages and receive aggressive treatments.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, the ADC histology subtype dominated in this population. No sex differences were observed in our study, which was similar to several other studies (4,9,23). Our study showed that when compared with the older cohort, younger patients were more likely to be diagnosed at advanced stages and receive aggressive treatments.…”
Section: Discussionsupporting
confidence: 93%
“…In our view, the reduced incidence might be attributed to economic development and improved living standards. Over the past few decades, poverty and geographical restraint have prevented some NSCLC patients from receiving standard cancer care services (9). Therefore, many NSCLC patients are diagnosed at advanced stages on initial examinations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations